2017
DOI: 10.1083/jcb.201607060
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the role of TPX2 in branching microtubule nucleation

Abstract: TPX2 is required for microtubule nucleation in mitosis, but the mechanism underlying its function is unclear. Alfaro-Aco et al. analyze the domains of TPX2 necessary for its activity and identify the minimal region required for branching microtubule nucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
116
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(128 citation statements)
references
References 47 publications
(105 reference statements)
11
116
1
Order By: Relevance
“…Spindle‐shrinking effects in Xenopus did not depend on Aurora A, but rather on a change in spindle microtubule distribution caused by increased recruitment of the cross‐linking Eg5 motor to spindle poles (Helmke & Heald, ). TPX2 also regulates microtubule nucleation in the spindle (Alfaro‐Aco, Thawani, & Petry, ; Petry, ; Petry, Groen, Ishihara, Mitchison, & Vale, ; Scrofani, Sardon, Meunier, & Vernos, ). TPX2 has thus emerged as a central player of spindle assembly and organization in a wide variety of cell types (Fu et al, ; Helmke, Heald, & Wilbur, ; Levy & Heald, ; Ma, Titus, Gable, Ross, & Wadsworth, ) and is overexpressed in many cancers (Chang et al, ; Neumayer, Belzil, Gruss, & Nguyen, ).…”
Section: Resultsmentioning
confidence: 99%
“…Spindle‐shrinking effects in Xenopus did not depend on Aurora A, but rather on a change in spindle microtubule distribution caused by increased recruitment of the cross‐linking Eg5 motor to spindle poles (Helmke & Heald, ). TPX2 also regulates microtubule nucleation in the spindle (Alfaro‐Aco, Thawani, & Petry, ; Petry, ; Petry, Groen, Ishihara, Mitchison, & Vale, ; Scrofani, Sardon, Meunier, & Vernos, ). TPX2 has thus emerged as a central player of spindle assembly and organization in a wide variety of cell types (Fu et al, ; Helmke, Heald, & Wilbur, ; Levy & Heald, ; Ma, Titus, Gable, Ross, & Wadsworth, ) and is overexpressed in many cancers (Chang et al, ; Neumayer, Belzil, Gruss, & Nguyen, ).…”
Section: Resultsmentioning
confidence: 99%
“…Augmin is necessary to recruit g-TuRC to spindle microtubules (Goshima et al, 49 2007), and following the recombinant expression of augmin (Hsia et al, 2014), this activity was 50 confirmed using purified proteins (Song et al, 2018). In meiotic Xenopus egg extract, the Ran-51 regulated protein TPX2 is released near chromatin (Gruss et al, 2001), where it stimulates 52 branching microtubule nucleation (Petry et al, 2013), potentially by activating g-TuRC (Alfaro-53 Aco et al, 2017). Recently, TPX2 was also observed to form a co-condensate with tubulin along 54 microtubules, which enhances the kinetic efficiency of branching microtubule nucleation (King 55 and Petry, 2019).…”
Section: Introduction 30mentioning
confidence: 99%
“…The formation of augmin-dependent 12 branched MT arrays was also visualized in Xenopus egg extracts (Petry et al, 2013) although 13 the postulated steps of branching MT nucleation: 1) augmin binding, 2) recruitment of -TuRC to 14 mother MTs, and 3) nucleation of daughter MTs were not directly observed. In the egg extract 15 model, both RanGTP and its downstream target Targeting Protein for Xklp2 (TPX2), which 16 mediate acentrosomal spindle assembly around DNA (Groen et al, 2009;Maresca et al, 2009) 17 have been implicated in promoting branching MT nucleation (Alfaro-Aco et al, 2017;Petry et 18 al., 2013). Interestingly, these factors are unlikely to contribute to branching MT nucleation in 19 interphase cortical MT arrays in plant cells as both RanGTP and plant TPX2 are nuclear during 20 interphase (Vos et al, 2008).…”
mentioning
confidence: 99%
“…While the occurrence of shallow 9 angle/parallel branching events cannot be ruled out, we could not confidently identify bona-fide 10 parallel branch events, as defined by daughters originating from a mother-associated γ-TuRC, 11 because parallel MTs were bundled during cytokinesis. It should be noted that augmin depletion 12 in Arabidopsis, resulted in a majority of nucleation events (63%) becoming parallel (Liu et al, 14 TPX2 is a highly conserved protein and its activity has been associated with multiple 15 roles in mitosis, such as, spindle assembly (Gruss et al, 2001;Gruss et al, 2002;Ma et al, 16 2010;Wadsworth, 2015;Wittmann et al, 2000), MT nucleation, and MT stabilization (Alfaro-Aco 17 et al, 2017;Groen et al, 2009;Petry et al, 2013;Reid et al, 2016;Roostalu and Surrey, 2017).…”
mentioning
confidence: 99%